2021
DOI: 10.1111/bre.12585
|View full text |Cite
|
Sign up to set email alerts
|

The Rosebank Field, NE Atlantic: Volcanic characterisation of an inter‐lava hydrocarbon discovery

Abstract: The Rosebank Field is located in the Faroe-Shetland Basin and hosts hydrocarbons within siliciclastic sediments interlayered with volcanic packages of the Late Paleocene to Early Eocene aged Flett Formation. Within this study the volcanic sequences are investigated based on an integrated appraisal of available drill cuttings, sidewall cores, core and wireline logs including image log and geochemical logs from eight wells supported by 3D seismic data. The Rosebank lower (RLV), middle (RMV) and upper (RUV) volca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 102 publications
(180 reference statements)
0
14
0
Order By: Relevance
“…Detailed logging of the volcanic facies was undertaken by compiling graphic facies logs for each core followed by the development of a volcanic facies and intra‐facies scheme (e.g. Jerram, 2002; Millett et al., 2021; Single & Jerram, 2004; Watton et al., 2013) which encompassed all the encountered facies. Industry standard petrophysical RCA (routine core analysis) data was available for this study including Klinkenberg corrected gas permeability, helium porosity and grain density which were screened to ensure only analyses made on robust cores were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed logging of the volcanic facies was undertaken by compiling graphic facies logs for each core followed by the development of a volcanic facies and intra‐facies scheme (e.g. Jerram, 2002; Millett et al., 2021; Single & Jerram, 2004; Watton et al., 2013) which encompassed all the encountered facies. Industry standard petrophysical RCA (routine core analysis) data was available for this study including Klinkenberg corrected gas permeability, helium porosity and grain density which were screened to ensure only analyses made on robust cores were included.…”
Section: Methodsmentioning
confidence: 99%
“…Jerram et al, 2019;Millett et al, 2015;Planke, 1994). The lithofacies scheme presented in Figure 14 incorporates the main facies and intra-facies elements identified based on the core-log integration, modified after Millett et al (2021) to incorporate the more evolved and pyroclastic lithofacies of the RDG.…”
Section: Wireline Volcanic Facies Assessmentmentioning
confidence: 99%
“…The rapid fall of erupted volcanic breccia and tuff results in a highly heterogeneous deposit that shows in seismic data as chaotic reflections with poor‐continuity (e.g. Millett et al, 2021; Planke et al, 2017; Table 4c). The stratigraphic occurrence of pyroclastic facies underlying lava‐flow facies suggests they mark the initiation of a volcanic eruption and may potentially be altered by subsequent lava flows (Table 4c).…”
Section: Discussionmentioning
confidence: 99%
“…Flowing lava will naturally seek out existing topographical lows, which in these settings are often the hanging walls of rift bounding normal faults (e.g. Millett et al, 2021; Schofield & Jolley, 2013; Zanchetta et al, 2004). D’Elia and Martí (2013), working in the Lower and Upper members of the Sañicó Formation of the Jurassic Neuquén basin, Argentina, suggested that thick lava units deposited in the immediate hanging wall of the basin's boundary faults reduced topography within rift depocentres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation